Impacto en las instituciones prestadoras de salud (IPS) privadas frente al impago de cartera por parte de las entidades promotoras de salud (EPS). (2023)
Health in Colombia has experienced several changes over the years; Recounting its history, it begins with the Social Security security system in 1946, the current system that Colombians have with Law 100 of 1993, and more recently the proposal for health reform in 2023. . In the health system in Colombia currently, there are deficiencies in its service due to economic, social, political and cultural factors, which causes delays and inconveniences when providing the service.